Using of response surface methodology for optimization of biohydrogen production by Clostridium sp. tr2 isolated in Vietnam - Thu Huyen, Nguyen Thi; Yen, Dang Thi; Yen, Nguyen Thi; Nga, Vuong Thi; Hien, Lai Thuy (Academia Journal of Biology, 2013)
Biohydrogen is a clean, renewable, sustainable energy resource due to the highest energy density among all fuels and its combustion has no contribution to the environmental pollution and climate change. Biohydrogen production depends on a number of nutritional and environmental variables. The present paper is to determine the optimum condition for enhanced hydrogen production by a fermentative hydrogen-producing bacterium (designated as Clostridium sp. Tr2) isolated from buffalo-dung in Vietnam. The response surface methodology (RSM) was employed to determine the mutual eﬀects of glucose, yeast extract and iron concentration on its hydrogen production in a batch condition. RSM analysis showed that the highest hydrogen production potential (Ps) was obtained under the condition of 10.18 g L-1 glucose, 2.5 g L-1 yeast extract and 58 mg L-1 FeSO4.7H2O. All three factors had signiﬁcant inﬂuences on the Ps. Glucose and iron concentration, yeast extract and iron concentration were interdependent or there was a signiﬁcant interaction on Ps. Glucose and yeast extract concentration was slightly interdependent, or their interactive effect on Ps was not signiﬁcant. Under optimum conditions, the maximum H2 volume of 1080 ml (L medium)-1 were found after 22 h facultative anaerobic fermentation. The experiment results show that the RSM analysis with the central composite design was useful for optimizing the biohydrogen-producing process by newly isolated Clostridium sp. Tr2 in Vietnam